Three’s Company: Coexistence of Silicosis, Scleroderma, and Sjogren Syndrome in a Single Patient - Ziebelman, Alexis; Raibman-Spector, Shir; Gendelman, Omer (Case Reports in Rheumatology, 2022)
We describe a patient who presented with silicosis, scleroderma, and Sjogren syndrome all at the same time. The diagnoses in this case are all associated with continuous exposure to crystalline silica at the patient’s workplace. The following report discusses this unique presentation.